Fabrication of Porous Ag/TiO(2)/Au Coatings with Excellent Multipactor Suppression - Wu, Duoduo (Sci Rep, 2017)
Porous Ag/TiO(2)/Au coatings with excellent multipactor suppression were prepared by fabrication of porous Ag surface through two-step wet chemical etching, synthesis of TiO(2) coatings by electroless-plating-like solution deposition and deposition of Au coatings via electroless plating. Porous structure of Ag surface, TiO(2) coatings on porous Ag surface and Au coatings on porous Ag/TiO(2) surface were verified by field-emission scanning electron microscopy, the composition and crystal type of TiO(2) coatings was characterized by X-ray photoelectron spectroscopy and X-ray diffraction. Secondary electron yield (SEY) measurement was used to monitor the SEY coefficient of the porous Ag coatings and Ag/TiO(2)/Au coatings. The as-obtained porous Ag coatings were proved exhibiting low SEY below 1.2, and the process was highly reproducible. In addition, the porous Ag/TiO(2)/Au coatings showed excellent multipactor suppression with the SEY 1.23 and good environmental stability. It is worth mentioning that the whole preparation process is simple and feasible, which would provide a promising application in RF devices.